Positive–Negative Asymmetry in the Evaluations of Political Candidates. The Role of Features of Similarity and Affect in Voter Behavior - Falkowski, Andrzej; Jabłońska, Magdalena (Frontiers in Psychology, 2018)
In this study we followed the extension Tversky’s research on about features of similarity by with its application to open sets. Unlike the original closed-set model, in which a feature was shifted between a common and a distinctive set, we investigated how addition of new features and deletion of existing features affected similarity judgements. The model was tested empirically in a political context and we analyzed how positive and negative changes in a candidate’s profile affect the similarity of the politician to his or her ideal and opposite counterpart. The results showed a positive-negative asymmetry in comparison judgements, where enhancing negative features (distinctive for an ideal political candidate) had a greater effect on judgements than operations on positive (common) features. However, the effect was not observed for comparisons to a bad politician. Further analyses showed that in the case of a negative reference point, the relationship between similarity judgements and voting intention is was mediated by the affective evaluation of the candidate.